A nova política de habitação de interesse social no Pará (2007-2010): avanços e limites - HOLANDA, Anna Carolina Gomes (Universidade Federal do Pará, 2012)
This dissertation presents a reflection on the advances and limitations of the new National Social Interest Housing System policy in Pará State, Brazil, in the period 2007 to 2010. It identifies the main obstacles for its implementation considering the performance of the different levels of Government. The National Social Interest Housing System can be considered an advance for the national policy and it is a result of the trajectory and know-how from the movements related to the Urban Reform discussion in the country. It introduces a new institutional arrangement based on the strengthening of the federative pact, greater participation and social control, with greater allocation of resources and the expansion of the role of the State Government. This study examines the decentralization strategies implemented by this new policy, as well as the results, especially those achieved by the municipalities in Pará, with regard to access to federal funds and the execution of actions in this sector. The literature addresses the housing and urban issues, State and social policies, social policy decentralization, housing policy in Brazil and Pará and urbanization in the Amazon, with focus on Pará State. A documental research was carried out, along with interviews with representatives of the Federal, State and Municipal Governments as well as representatives of social and popular movements. The results indicate that, despite the advances in structuring a national system and the achievement of important spaces for participation at the federal level, the strategies of decentralization are still fragile, which may represent a limitation to the consolidation of the National Social Interest Housing System.